Microbiologically Induced Corrosion Associated with the Wet Storage of Subsea Pipelines (Wet Parking) - Machuca Suarez, Laura (CRC Press, 2017)
BBefore and after commissioning of subsea equipment and pipelines, it is typically the case that operational challenges and delays can lead to prolonged periods of equipment shutdown. To ensure pipelines remain within design specifications, pipelines are filled with treated fluids until commissioning takes place or until operations are restored. These lay-up periods are referred to as wet parking and are common to any subsea operation. The implications of this practice lie in the associated risk of chemical degradation when the wet lay-up period is prolonged beyond the anticipated date of start-up. In addition, Microbiologically Influenced Corrosion in the Upstream Oil and Gas Industry if wet parking or pipeline suspension is expected to take place after several years of production, the risk of corrosion increases due to contamination of the pipe internal surface with hydrocarbons, deposits, and biofilms. Therefore, the selection of an appropriate chemical treatment for preservation of subsea pipelines and subsequent wet lay-up poses a significant dilemma for offshore engineers. This chapter discusses several challenges related to the wet parking of subsea pipelines, in particular, the risk of microbiologically influenced corrosion in pipelines filled with treated seawater and monoethylene glycol.